Engagement under revision: How Iranian scholars negotiate the arguability of their texts - Maniati, Mahmood; Jalilifar, Alireza; Mashhadi, Amir; Hemmati, Ali (Complutense Journal of English Studies, 2020)
Non-native English speaking (NNES) scholars face great hardship when they attempt to publish in English. Upon submitting their manuscripts to English-language journals, these scholars usually receive comments from the reviewers criticizing the rhetorical structures they adopt. One of these criticisms is concerned with how they manage the relationship between the author and the potential addressee; that is, the scholars’ expression of their attitude and the way they adjust the certainty of their claims and establish a relationship with their readers. This study attempted to examine how the acceptably revised manuscripts written by Iranian scholars differ from the originally submitted versions regarding the changes happening to the Engagement system of the texts. Findings showed Iranian scholars’ inadequate knowledge of the interpersonal weightings of the lexico-grammatical structures they used —hence giving undue credit to other researchers in the field— was mitigated by giving more space to the feature of distance citations, thereby failing to achieve a typically sound and rigorous argumentation.